Changes in chondrocyte gene expression following in vitro impaction of porcine articular cartilage in an impact injury model. Issue 3 (1st October 2012) - Ashwell, Melissa S.; Gonda, Michael G.; Gray, Kent; Maltecca, Christian; O'Nan, Audrey T.; Cassady, Joseph P.; Mente, Peter L.
Abstract Our objective was to monitor chondrocyte gene expression at 0, 3, 7, and 14 days following in vitro impaction to the articular surface of porcine patellae. Patellar facets were either axially impacted with a cylindrical impactor (25 mm/s loading rate) to a load level of 2, 000 N or not impacted to serve as controls. After being placed in organ culture for 0, 3, 7, or 14 days, total RNA was isolated from full thickness cartilage slices and gene expression measured for 17 genes by quantitative real‐time RT‐PCR. Targeted genes included those encoding proteins involved with biological stress, inflammation, or anabolism and catabolism of cartilage extracellular matrix. Some gene expression changes were detected on the day of impaction, but most significant changes occurred at 14 days in culture. At 14 days in culture, 10 of the 17 genes were differentially expressed with col1a1 most significantly up‐regulated in the impacted samples, suggesting impacted chondrocytes may have reverted to a fibroblast‐like phenotype. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 385–391, 2013